Patient and hospital characteristics that influence incidence of adverse events in acute public hospitals in Portugal: a retrospective cohort study - Sousa, Paulo (Int J Qual Health Care, 2018)
OBJECTIVE: To analyse the variation in the rate of adverse events (AEs) between acute hospitals and explore the extent to which some patients and hospital characteristics influence the differences in the rates of AEs. DESIGN: Retrospective cohort study. Chi-square test for independence and binary logistic regression models were used to identify the potential association of some patients and hospital characteristics with AEs. SETTING: Nine acute Portuguese public hospital centres. PARTICIPANTS: A random sample of 4250 charts, representative of around 180 000 hospital admissions in 2013, was analysed. INTERVENTION: To measure adverse events based on chart review. MAIN OUTCOME MEASURE: Rate of AEs. RESULTS: Main results: (i) AE incidence was 12.5%; (ii) 66.4% of all AEs were related to Hospital-Acquired Infection and surgical procedures; (iii) patient characteristics such as sex (female 11%; male 14.4%), age (≥65 y 16.4%; <65 y 8.5%), admission coded as elective vs. urgent (8.6% vs. 14.6%) and medical vs. surgical Diagnosis Related Group code (13.4% vs. 11.7%), all with p < 0.001, were associated with a greater occurrence of AEs. (iv) hospital characteristics such as use of reporting system (13.2% vs. 7.1%), being accredited (13.7% vs. non-accredited 11.2%), university status (15.9% vs. non-university 10.9%) and hospital size (small 12.9%; medium 9.3%; large 14.3%), all with p < 0.001, seem to be associated with a higher rate of AEs. CONCLUSIONS: We identified some patient and hospital characteristics that might influence the rate of AEs. Based on these results, more adequate solutions to improve patient safety can be defined.